The impact of stock liquidity on cash holdings: an empirical investigation of listed firms in Malaysia - Kwan, Shiang Shen (2020)
Over the past few decades, the tremendous growth in the level of cash held by firms around the world has raised academic interest among scholars to understand why firms are accumulating so much cash. While most research on the determinants of cash holdings has focused on firm-specific characteristics, there were only a few attempts that investigated how external factors like stock prices and returns would influence a firm’s cash holdings. Since an increase in stock liquidity, an indicator of how easily a stock can be sold or bought without affecting the stock price, will decrease the cost of capital, firms are expected to hold less cash as these firms can raise capital at a lower transaction cost with fewer constraints. However, there is a counter-argument which proposes that an increase in stock liquidity will incentivise firms to hold more cash to increase their capacity to reap the benefits of stock repurchase, implying that a firm’s financial policy is more inclined toward managing equity misvaluation than real investments.